2023
DOI: 10.1111/apt.17386
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: Real‐world effectiveness and safety of ustekinumab in patients with ulcerative colitis

Abstract: Summary Background Evidence on real‐world outcomes of ustekinumab for ulcerative colitis (UC) patients is needed. Aims To summarise evidence on the real‐world outcomes of ustekinumab for UC and conduct a meta‐analysis of effectiveness and safety data. Methods A systematic search was conducted through September 2022 in electronic databases for observational studies evaluating ustekinumab for UC. A random‐effects meta‐analysis model was used to calculate the pooled effect sizes (percentages or incidence rates [I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
(260 reference statements)
0
8
0
2
Order By: Relevance
“…A meta-analysis of RW studies included a total of 19 studies, with 3786 patients, of which >92% were previously treated with any biologic, 61.1% with both anti-TNF-α and VDZ, and 16.4% with any biologic and tofacitinib [ 91 ]. Among the UC patients, 45.4% were in clinical remission by weeks 8, 43.8% (38.4–49.2%) by weeks 12–16, 44.6% by month 6, and 50.6% by month 12.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis of RW studies included a total of 19 studies, with 3786 patients, of which >92% were previously treated with any biologic, 61.1% with both anti-TNF-α and VDZ, and 16.4% with any biologic and tofacitinib [ 91 ]. Among the UC patients, 45.4% were in clinical remission by weeks 8, 43.8% (38.4–49.2%) by weeks 12–16, 44.6% by month 6, and 50.6% by month 12.…”
Section: Resultsmentioning
confidence: 99%
“…In UC, a systematic review of RW data found that patients with AEs ranged from 2.6% to 32% [ 89 ]. In another recent systematic review with a meta-analysis of RW, the incidence rates (iRs) of colectomy, mild and severe AEs, and serious infections were 4.8, 7.9, 0.8, and 0.3 per 100 patient-years, respectively [ 91 ]. The most common non-infectious AE, except IBD exacerbation, was arthralgia (1.94%), followed by a skin rash (1.55%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No adverse events were observed in our cohort. In a systematic review of real-world data [ 15 ] and results from randomized clinical trials [ 5 , 16 ], an acceptable safety profile of UST in patients with UC was reported. The results of our real-world safety data validate these results, although the number of patients included in our study was small.…”
Section: Discussionmentioning
confidence: 99%
“…Ustekinumab (UST, marketed as Stelara; Janssen Biotech, Inc, Horsham, PA, USA) represents a fully human IgG1 monoclonal antibody designed to target the shared p40 subunit of interleukin 12 (IL12) and 23 (IL23) and effectively inhibit the T-helper 1 (Th1) and T-helper 17 (Th17) pathways, which play crucial roles in CD [ 8 , 10 , 11 , 12 , 13 , 14 ]. UST has shown favourable results in real-life studies [ 15 , 16 , 17 , 18 ] and a good safety profile [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%